2020
DOI: 10.31234/osf.io/zxhw3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short Research Report: Does Playing Apart Really Bring us Together? Investigating the Link Between Perceived Loneliness and the Use of Video Games During the COVID-19 Pandemic.

Abstract: During the COVID-19 pandemic, several countries implemented social distancing measures to contain virus transmission. However, these vital safety measures have the potential to impair mental health or well-being, for instance, from increased perceived loneliness. Playing social video games may offer a way to continue to socialize while adhering to social distancing measures. To examine this issue further, the present online survey investigated social gaming during the pandemic and its association to perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Video games as coping tools during challenge life circumstances is well documented ( Caro & Popovac, 2021 ; Iacovides & Mekler, 2019 ). Individuals have used video games to cope with pandemic-related stress ( Cahill, 2021 ; Eden, Johnson, Reinecke, & Grady, 2020 ; Kleinman, Chojnacki, Seif El-Nasr, & El-Nasr, 2021 ; Nabi, Wolfers, Walter, & Qi, 2021 ; Nebel & Ninaus, 2020 ), including AC:NH ( Barr & Copeland-Stewart, 2021 ). Moreover, video games ( Barr & Copeland-Stewart, 2021 ) including AC:NH ( Johannes, Vuorre, & Przybylski, 2021 ) tied to well-being during the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Video games as coping tools during challenge life circumstances is well documented ( Caro & Popovac, 2021 ; Iacovides & Mekler, 2019 ). Individuals have used video games to cope with pandemic-related stress ( Cahill, 2021 ; Eden, Johnson, Reinecke, & Grady, 2020 ; Kleinman, Chojnacki, Seif El-Nasr, & El-Nasr, 2021 ; Nabi, Wolfers, Walter, & Qi, 2021 ; Nebel & Ninaus, 2020 ), including AC:NH ( Barr & Copeland-Stewart, 2021 ). Moreover, video games ( Barr & Copeland-Stewart, 2021 ) including AC:NH ( Johannes, Vuorre, & Przybylski, 2021 ) tied to well-being during the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A relationship between family video game play and family connectedness exists ( Balmford & Davies, 2020 ; Wang, Taylor, & Sun, 2018 ). The sociability affordance of video games is well documented, including for coping ( Collins & Cox, 2014 ), especially during difficult life situations ( Caro & Popovac, 2021 ; Iacovides & Mekler, 2019 ), including the pandemic ( Cmentowski & Krüger, 2020 ; Marston & Kowert, 2020 ; Nebel & Ninaus, 2020 ), with AC:NH ( Kleinman et al, 2021 ; Ng, 2021 ). One study found an association between social actions in AC:NH and decreased levels of loneliness ( Lewis, Trojovsky, & Jameson, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, individuals increased their use of mediated communication during the pandemic, which was beneficial for well-being (Brown & Greenfield, 2021; Gabbiadini et al, 2020). This included video games, which is not surprising, as the sociability affordance of video games is well documented (Jiow et al, 2017), even during the COVID-19 pandemic (Cmentowski & Krüger, 2020; Nebel & Ninaus, 2020), particularly with AC:NH (Comerford, 2021; Kleinman et al, 2021; Ng, 2021). We also note that other work has found that social aspects of video game play can enhance video game-related coping and recovery (Collins & Cox, 2014).…”
Section: Resultsmentioning
confidence: 94%
“…The analysis was conducted using SPSS Statistics (IBM, 2020), R (R Core Team, 2020), and the R packages psych (Revelle, 2020), ggplot2 (Wickham, 2016), and GGally (Schloerke et al, 2020). The dataset and analysis code are publicly available (Nebel and Ninaus, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Further, in contrast to broad descriptions of "screen time" or gaming, the current study aimed at providing a differential perspective by not only investigating different modes of gaming (i.e., single-player vs. multiplayer) but also different motives for gaming. In response to recent calls for transparency in the social sciences (e.g., Vazire, 2017) and gaming research (Vornhagen et al, 2020), we strived for a transparent workflow and made our data and analysis code openly (Nebel and Ninaus, 2020) available so that others can easily build upon our research.…”
Section: Introductionmentioning
confidence: 99%